Arkansas’s cotton plantocracy: the role of POWs in establishing postwar labor systems - Kruger, Cole T. (Kansas State University, 2023)
This project examines how the cotton plantocracy of Arkansas during World War II, with the help of county and state officials, manipulated the military and federal government to use prisoners of war (POWs) to suppress the wages of local labor and set up their postwar future. This practice had lasting effects on labor in the South as POWs remained in the fields until the spring 1946, which allowed the planters to transition to Mexican migrant laborers and eventually mechanization. Through manipulation by the planter elite and complicit government officials, the most significant number of camps and POWs devoted to one crop occurred in the cotton fields of the Mississippi Delta region of Arkansas, Mississippi, and Louisiana. Local planters, agriculture organizations, and state representatives in Arkansas, such as Congressman Ezekiel C. "Took" Gathings and Arkansas Governor Homer Adkins, exaggerated their labor needs and continually lobbied for POW camps to spark the cotton economy in the Mississippi Delta despite objections from labor organizations, such as the Southern Tenant Farmers' Union (STFU), a biracial union of sharecroppers and farmworkers. Furthermore, Arkansas’ segregationist practices influenced labor policies, as maintaining a distinct racial hierarchy remained a priority through these years of transition. Only certain people could labor in the cotton fields, with Japanese American internees in Arkansas being notably excluded. This dissertation relies on an interdisciplinary methodology, as the nature of this topic blends elements of labor, race, military, and Southern history along with economic and sociological aspects. Since the move towards mechanization was a gradual postwar process, Mexican nationals or braceros came to replace German and Italian POWs after 1946 as an inexpensive and removable labor force that the planters could employ to manipulate local labor wages until mechanical cotton harvesters forever changed Southern labor systems.
Keywords: POWs; Mississippi Delta; Cotton; Planter; Labor; South